SURVEY OF KNOWLEDGE AND ATTITUDE ABOUT MIDWIFE CIRCUMCISION THE GIRL IN THE HEALTH LHOKSUKON DISTRICT NORTH ACEH - Agustina (JURNAL KESEHATAN ALMUSLIM, 2021)
Circumcision is performed on women no health benefits, otherwise these activities have a negative impact, namely the physical impact is felt women include pain, bleeding and infection, psychological impact: fear and trauma. Therefore WHO has declared against any form of medicalization of female circumcision. (WHO, 2010). In the study are still many midwives who practice circumcision in girls. To determine the knowledge and attitudes picture midwife about circumcision of girls in the clinic Lhoksukon North Aceh district. This research is descriptive, place and time of the study, namely in the health center Lhoksukon on July 2016. The entire population is midwife in Puskesmas Lhoksukon district, as many as 39 people. A sampling technique that uses total sampling technique that is the entire population sampled totaling 39 people. data obtained by distributing a questionnaire given to respondents, the data processed by means of editing, coding, Transferring and tabulating. Knowledge midwife about circumcision of girls are in the majority category enough (44%), and the attitude of the majority of midwives are in the negative category (54%). Conclusion: The results that midwives knowledge about the circumcision of girls are in the majority and the category enough midwives majority attitude is negative.